3D printed porous microgel for lung cancer cells culture in vitro. (15th November 2021) - Hu, Qipeng; Liu, Xuan; Liu, Haofan; Yang, Ling; Yuan, Xin; Chen, Yuwen; Wu, Wenbi; Luo, Jing; Long, Jianlin; Huang, Meijuan; Gou, Maling
Graphical abstract: Highlights: A novel method for 3D lung cancer cell culture via 3D printed porous microgel. The ROCK pathway in 3D cultured lung cancer cells is similar to the solid tumors. Overexpression of the ROCK pathway enhances paclitaxel resistance in lung cancers. Abstract: Currently, in vitro cancer cell culture technology is very important for cancer research. Existing studies have shown that two-dimensional (2D) cell environment may cause significant differences from tumor cells in vivo, resulting in high failure rates when the therapies developed in 2D tumor models translated to the clinic. And compared with 2D culture, the isotropic three-dimensional (3D) culture can construct an environment more similar to that in the body. Here, we utilized 3D printed porous microgel to culture for lung cancer cell and also explored possible mechanism of how 3D culture environment regulates actin cytoskeleton. Compared with 2D cultured lung cancer cells, cells in porous microgel are more similar to those extracted from the existing gold standard: mouse transplanted tumors, in terms of the ROCK-actin pathway. In addition, this study also revealed that ROCK pathway altered by environment played an important role in regulating the drug sensitivity of lung cancer cells. Hence, this 3D printed porous microgel is a promising lung cancer cell culture method, which shows potentional application in future cancer research and drug development.